Traffic management system based on wsn in Kuwait: an initial design - Taha, Imad; Alkandari, Abdulrahman; alnasheet, Meshal (2012)
This paper discusses traffic problems in the world and emphasizes on Kuwait city as case study. Many of these problems can be solve by building a Traffic Management System based on a Wireless Sensor Network (WSN). TMS is an innovative design for the road that saves time and money for the driver. This solution creates a city of intelligence, which can be control automatically through sensors. Some of the sensor nodes were portable and fixed that spread in buildings, streets, cars and traffic signals. We use two kinds of WSN motion sensors and physical sensors. We also use two kinds of WSN nodes: special-purpose sensor nodes and generic sensor nodes. Zigbee platform use to communicate between nodes in short speed and reduce energy consumption. The Database Management Systems (DBMS) supports a geospatial database by offering the GIS services such as fingerprints, photos and videos. The functionality of Network Operation Center (NOC) to supervise, maintains, and monitors the wireless network. GPS/routing protocols use to detect the location with longitude and latitude date information with Geographic information system (GIS) to discover geographic location for the city maps. The routing protocols were cheaper and provide same functionality as GPS. Our initial design describes the physical layer to explain the connectivity path from (NOC) to vehicle then network layer depending on routing protocols lastly, application layer shows the dashboard monitor system that controlled by (NOC) and how it solve a different issues in traffic problems.